Nodular hidradenoma presenting as a scalp swelling: A case report and histopathological analysis (Indian Journal of Case Reports, 2026)
Among the myriad pathologies presenting as scalp swellings, benign adnexal tumors are a very small subset, with nodular hidradenoma being a rare cause. Nodular hidradenoma is a skin tumor with eccrine or apocrine differentiation, mostly seen in the scalp or in the axilla. These tumors can raise the suspicion of being malignant in nature, especially due to their varied presentation as having irregular margins and pain, rapid increase in size, and bleeding, or ulceration. As no clear-cut diagnosis can be made till now, a histopathological examination is performed, it presents a challenge in establishing a diagnosis and its management. We encountered a case of a woman presenting with a scalp swelling with atypical features, which raised the suspicion of it being a pyogenic granuloma, that is either highly vascular or a malignancy due to its firm consistency and irregular margins with multiple bleeding points. The case with its diagnostic dilemma and its confirmation in histopathological examination has been presented here